Exploring spices production at sustainable basis - Janakiram, T; Babu, Nirmal; Dinesh, R; Srinivasan, V; Sheeja, T E (Indian Horticulture, 2019)
There is a great scope to improve the productivity of major spices by adopting technologies that will help bridge the gap between potential yields realized in the research stations/progressive farmers’ plots and those realized in other marginal farmers’ plots. While there is a little scope for enhancing the area under spices in traditional belts of the country, we need to focus on newer niches where the potential for spices cultivation is immense. Fortunately, spices cultivation is now spreading to non-traditional areas and is being expanded in the North-Eastern Hill region through the Tribal Sub Plan, which will subsequently help in including several niche areas of spice cultivation, where opportunities and skill sets for the future exists. In addition, research programmes are to be intensified in the area of high-value compounds in spices for possible drug formulations and to develop nutrigenomics and pharmacogenomics as a composite technology in the area of bioactive compounds. India can withstand competition only by increasing productivity and reducing cost of cultivation, leading to low cost per unit of production. Nurturing and improving sound techniques on precision farming, protected cultivation and urban horticulture can help in surmounting the challenges posed by other growing countries. A well reasoned and cohesive application of cutting edge research, institutional support for development and creative policy initiatives can ensure a vibrant spices sector in our country, says Dr Janakiram, ADG (Hort. Sci.) at the ICAR Headquarters.